Decreases in encounter rate of endangered Northeast Pacific humpback whales in Southern Costa Rica: Possible changes in migration pattern due to warming events ... : انخفاض في معدل مواجهة الحيتان الحدباء المهددة بالانقراض في شمال شرق المحيط الهادئ في جنوب كوستاريكا: التغيرات المحتملة في نمط الهجرة بسبب أحداث الاحتباس الحراري ... - Lili Pelayo‐González; David Herra-Miranda; Juan Diego Pacheco-Polanco; Héctor M. Guzmán; Sierra Goodman; Lenin Oviedo (OpenAlex, 2022)
Warming events in the Pacific Ocean are becoming more frequent, intense, and on a larger temporal and spatial scale. This has caused critical habitats of marine species to lose their quality and marine organisms respond by modifying their critical feeding and reproduction behaviors, as well as their distribution. The Northeast Pacific humpback whale of the Central America distinct population segment (DPS) remains Endangered due to its small population size and because its response to climate change and human interventions is unknown. In this work, we showed the encounter rates of humpback whales in their breeding grounds in Costa Rica for breeding seasons comprised in the period 2000-2020. We analyze the influence of climatic indices that influence the Pacific and environmental variables related to temperature and productivity in the feeding grounds of this population (United States). We hypothesize that the more intense the warming events, the fewer humpback whales complete their migration to Costa Rica. We ... : أصبحت أحداث الاحترار في المحيط الهادئ أكثر تواتراً وشدة وعلى نطاق زمني ومكاني أكبر. وقد تسبب ذلك في فقدان الموائل الحرجة للأنواع البحرية لجودتها واستجابة الكائنات البحرية عن طريق تعديل سلوكيات التغذية والتكاثر الحرجة، وكذلك توزيعها. لا يزال الحوت الأحدب في شمال شرق المحيط الهادئ من شريحة السكان المتميزة في أمريكا الوسطى (DPS) مهددًا بالانقراض بسبب صغر حجمه السكاني ولأن استجابته لتغير المناخ والتدخلات البشرية غير معروفة. في هذا العمل، أظهرنا معدلات مواجهة الحيتان الحدباء في مناطق تكاثرها في كوستاريكا لمواسم التكاثر التي تشكلت في الفترة 2000-2020. نقوم بتحليل تأثير المؤشرات المناخية التي تؤثر على المحيط الهادئ والمتغيرات البيئية المتعلقة بدرجة الحرارة والإنتاجية في مناطق التغذية لهذه الفئة من السكان (الولايات المتحدة). نحن نفترض أنه كلما زادت حدة أحداث الاحترار، كلما قل عدد الحيتان الحدباء التي تكمل هجرتها إلى كوستاريكا. نستنتج أن الحيتان الحدباء من هذه المجموعة يمكن أن تجد مناطق مواتية حرارياً في خطوط العرض المتوسطة (على سبيل المثال، السواحل المكسيكية الغواتيمالية)، والتي يمكن أن تكون مرتبطة بالنقصان في وجود ...